2020
DOI: 10.1002/adma.202003897
|View full text |Cite
|
Sign up to set email alerts
|

A Machine‐Fabricated 3D Honeycomb‐Structured Flame‐Retardant Triboelectric Fabric for Fire Escape and Rescue

Abstract: Fire disaster is one of the most common hazards that threaten public safety and social development: how to improve the fire escape and rescue capacity remains a huge challenge. Here, a 3D honeycomb‐structured woven fabric triboelectric nanogenerator (F‐TENG) based on a flame‐retardant wrapping yarn is developed. The wrapping yarn is fabricated through a continuous hollow spindle fancy twister technology, which is compatible with traditional textile production processes. The resulting 3D F‐TENG can be used in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 41 publications
3
107
0
1
Order By: Relevance
“…Fortunately, since the invention of the triboelectric nanogenerator (TENG) in 2012 [ 5 7 ], wearable electronics provide new dawn and reengineering for sensing and energy harvesting [ 8 10 ]. On account of the advantages of TENGs, such as easy structural design [ 11 , 12 ], low cost [ 13 ], high conversion efficiency [ 14 , 15 ], and broad range of applications [ 16 ], the coupling effect of contact electrification (CE) and electrostatic induction can be achieved between any materials [ 6 , 17 ]. Therefore, the integration of general-purpose TENG technology with smart fabrics brings new vitality and more possibilities to the next generation of wearable electronics [ 18 , 19 ], personal healthcare [ 20 , 21 ], and human–computer interfaces [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, since the invention of the triboelectric nanogenerator (TENG) in 2012 [ 5 7 ], wearable electronics provide new dawn and reengineering for sensing and energy harvesting [ 8 10 ]. On account of the advantages of TENGs, such as easy structural design [ 11 , 12 ], low cost [ 13 ], high conversion efficiency [ 14 , 15 ], and broad range of applications [ 16 ], the coupling effect of contact electrification (CE) and electrostatic induction can be achieved between any materials [ 6 , 17 ]. Therefore, the integration of general-purpose TENG technology with smart fabrics brings new vitality and more possibilities to the next generation of wearable electronics [ 18 , 19 ], personal healthcare [ 20 , 21 ], and human–computer interfaces [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, self-powered smart textiles combined with TENGs for accommodating the era of IoTs have been reported [ 37 40 ]. For example, a 3D honeycomb structure woven fabric triboelectric nanogenerator based on flame-retardant wrapping yarn was developed for fire escape and rescue [ 11 ]. A DC fabric TENG, which takes advantage of electrostatic breakdown phenomenon of clothes, can light up 416 serially connected light-emitting diodes [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To harvest this part of mechanical energy, single-electrode mode has been invented ( Figure 3 C). This mode has significant merits for energy harvesting in some special cases such as human working, finger typing, motion sensor, raindrop, and more ( Lin et al., 2014 ; Ma et al., 2020 ; Niu et al., 2014 ; Pu et al., 2017a ; Wu et al., 2018 ; Yang et al., 2013 ). The freestanding triboelectric-layer mode is also invented for harvesting mechanical energy from the free object ( Figure 3 D).…”
Section: Ac-tengmentioning
confidence: 99%
“…[ 18–20 ] Wearable TENGs based on textiles extract mechanical energy from the human body, actively sense body motion, and function in a wide range of conditions. [ 7,10–15,21–37 ] One of the authors previously reported the first single‐thread‐based TENG using a twisted multi‐thread stainless steel wire as the conducting electrode and silicone rubber as the triboelectric material. [ 11 ] However, the resulting TENG was neither stretchable nor elastic; therefore, a 1D serpentine sewing structure was proposed to overcome the mechanical limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,12,21–27 ] In most works, the individual triboelectric fibers remained inherently inextensible; as a result, the achieved stretchabilities of the reported TENG fabrics remain considerably limited (20–30% strain) as defined by the geometry of the fibers rather than the inherent mechanical properties. [ 7,10–15,21–34 ] Stretchable devices are more robust, comfortable, and versatile than inextensible devices, yet there is a lack of such intrinsically stretchable and elastic TENG fibers. [ 35–38 ]…”
Section: Introductionmentioning
confidence: 99%